Lawyers’ Use of the Website of the Supreme Judicial Council and the Gratifications Obtained from It Drawn Research Submitted for the Study of the Higher Professional Diploma - Abd, Ali Abbas Hashim; Al-Rahman., Zina Abd (ALBAHITH ALALAMI, 2022)
The field study of this paper focused on the motives for lawyers to use the website of the Supreme Judicial Council, and the gratifications achieved as a result of its use. This study sought to achieve a number of goals, including: 1. Monitoring the patterns of lawyers’ use of the website of the Supreme Judicial Council. 2. Determining the forms that lawyers use to interact on the website of the Supreme Judicial Council. This study is a descriptive in kind as the researcher relied on the ‘survey method’ in its study of the external audience (lawyers) using the questionnaire and scale toolThe questionnaire was distributed among a deliberately chosen sample, consisting of (160) lawyers who used the website of the Supreme Judicial Council. The study ended with a set of results, the most important of which are: A. It turns out: Lawyers’ use of the website of the Supreme Judicial Council is as follows: Lawyers’ use of the website which came in first place is of (on average twice a week), followed by second place is of (three times a week), and third is of (once a week). B. The results showed that: The utilitarian motives for lawyers’ use of the website were as follows: the one is ranked first (it keeps me in line with the development in my legal field), while the one ranked last (it gives me the opportunity to express my opinion on various legal cases). As for ritual motives, this category is ranked first (which contributes to the dissemination of legal texts that are useful to others), while the category (which helps to get rid of personal problems and forget them and the desire to have fun) is ranked last..